Perkuatan Struktur pada Bangunan Rumah Tinggal 3 Lantai - Anis Rosyidah; Rinawati Rinawati; Dimas Wiratenaya; Muhammad Amitabh Pattisia (Jurnal Poli-Teknologi, 2010)
Abstract Design on building a less mature may result in failure of the building functions. It can be seen from the emergence of cracks in structural elements. To handle these problems, to prevent any malfunction or possible collapse of the building, it is necessary to strengthen or repair the structural elements that are considered damaged. Damage to the structure elements can be seen from the comparison between the existing calculation of structural elements with ideal calculations buildings. If the ideal calculation is greater than the existing calculation of the structural elements considered necessary improvements. There are several options for strengthening methods. But the selection of methods must be based on the needs, circumstances and budget for strengthening the field itself. In this project the planners combine two methods for strengthening, the concrete jacketing and inject column. In each of these methods has advantages and disadvantages of each is conditioned by the field. Because of this, then inject column be the first choice at this stage of the selection method, this is because the advantages of this method can reduce the force in the received by beam. If this method can not be done due to limited field conditions will be the second selection method that is concrete jacketing. In this method of structural elements can add the capacity of strength to restrain load factored. Until the choosing of the appropriate method. Keyword: concrete strengthening, concrete jacketing, inject column.